Recent and Ongoing Horizontal Transfer of Mitochondrial Introns Between Two Fungal Tree Pathogens - Mayers, Chase G.; Harrington, Thomas C.; Wai, Alvan; Hausner, Georg (Frontiers in Microbiology, 2021)
Two recently introduced fungal plant pathogens (Ceratocystis lukuohia and C. huliohia) are responsible for Rapid ʻŌhiʻa Death (ROD) in Hawaii. Despite being sexually incompatible, the two pathogens often co-occur in diseased ʻōhiʻa sapwood, where genetic interaction is possible. We sequenced, annotated, and investigated 34 mitochondrial genomes of the two pathogens and related species. Ten mtDNA regions (two group I introns, seven group II introns, and an autonomous homing endonuclease gene) were heterogeneously present in C. lukuohia mitogenomes, which were otherwise identical. PCR-based surveys with specific primers showed that the ten regions had uneven geographic distribution amongst populations of C. lukuohia. Conversely, identical orthologs of each region were present in every studied isolate of C. huliohia regardless of geographical origin. Close relatives of C. lukuohia lacked or, rarely, had few and dissimilar orthologs of the ten regions, whereas most relatives of C. huliohia had identical or nearly identical orthologs. Each region included or worked in tandem with homing endonuclease genes or reverse transcriptase/maturases that could facilitate interspecific horizontal transfers from intron-minus to intron-plus alleles. These results suggest that the ten regions originated in C. huliohia and are actively moving to populations of C. lukuohia, perhaps through transient cytoplasmic contact of hyphal tips (anastomosis) in the wound surface of ʻōhiʻa trees. Such contact would allow for the transfer of mitochondria followed by mitochondrial fusion or cytoplasmic exchange of intron intermediaries, which suggests that further genomic interaction may also exist between the two pathogens.